Rational Design of Self-Emulsifying Pellet Formulation of Thymol: Technology Development Guided by Molecular-Level Structure Characterization and Ex Vivo Testing - Jan Macku; Katerina Kubova; Martina Urbanova; Jan Muselik; Ales Franc; Gabriela Koutna; Miroslava Pavelkova; David Vetchy; Josef Masek; Eliska Maskova; Jiri Brus (MDPI AG, 2022)
The growing need for processing natural lipophilic and often volatile substances such as thymol, a promising candidate for topical treatment of intestinal mucosa, led us to the utilization of solid-state nuclear magnetic resonance (ss-NMR) spectroscopy for the rational design of enteric pellets with a thymol self-emulsifying system (SES). The SES (triacylglycerol, Labrasol®, and propylene glycol) provided a stable o/w emulsion with particle size between 1 and 7 µm. The ex vivo experiment confirmed the SES mucosal permeation and thymol delivery to enterocytes. Pellets W90 (MCC, Neusilin®US2, chitosan) were prepared using distilled water (90 g) by the M1-M3 extrusion/spheronisation methods varying in steps number and/or cumulative time. The pellets (705-740 µm) showed mostly comparable properties-zero friability, low intraparticular porosity (0-0.71%), and relatively high density (1.43-1.45%). They exhibited similar thymol release for 6 h (burst effect in 15th min ca. 60%), but its content increased (30-39.6 mg/g) with a shorter process time. The M3-W90 fluid-bed coated pellets (Eudragit®L) prevented undesirable thymol release in stomach conditions (<10% for 3 h). A detailed, ss-NMR investigation revealed structural differences across samples prepared by M1-M3 methods concerning system stability and internal interactions. The suggested formulation and methodology are promising for other lipophilic volatiles in treating intestinal diseases.